Potret perbankan syariah Indonesia terkini : kajian kritis perkembangan perbankan syariah - Ghafur W., Muhammad (Muhammad Ghafur Wibowo) (Sleman, Yogyakarta : Biruni Press, 2007)
Development of Islamic banking in Indonesia
Includes bibliographical references (p. 152-158)
Keywords: Banks and banking -- Indonesia; Banks and banking -- Religious aspects -- Islam